Central Nerve System Malignant Tumors - Sepehr, Rahmani; Wong, Ling Shing (International Organization of a Scientific Research, 2014)
Tumors are classifying in two different types- non-cancerous (benign) or cancerous (malignant), which the malignant tumors are generally classified into meningiomas and gliomas tumors that varies in types. Some tumor occurrence are depend on the area that cells arise such as oligodendrogliomas, ependymomas and astrocytomas occur mostly from the meninges, which is outer part of brain and spinal cord. Even though they arise outside of the brain meningiomas do not be considered as brain tumor, because 85% of meningiomas are benign and can cure by surgery. Beside the three mentioned tumors meningiomas astrocytomas and glioblastomas mostly seen in adults, number of uncommon brain tumors containing medulloblastoma that arise from the cerebellum of primitive stem cells and most seen in children.